2016
DOI: 10.15580/gjbs.2016.6.121616215
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Makeshift Oil Refineries on the Macro-Invertebrates of the Nun River Estuary, Niger Delta, Nigeria

Abstract: Sampling was done in six sampling stations for one year (August, 2014-July, 2015) to investigate the impacts of makeshift oil refineries on the macro-invertebrates of the Nun River estuary in the Niger Delta region of Nigeria after over 3 years of chronic pollution of this estuary by the makeshift refinery activities. There was also a massive destruction of the benthic and mangrove associated macrofauna of the Nun River estuary and its tributaries. 18 species of benthic macro-invertebrates distributed among 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…Most fresh water resources in the area are linked to estuarine from where they emptied into the Ocean. The activities of makeshift oil refinery on Nun River estuary is having impact on the physicochemical characteristics of water, 50 sediment 51 and macro-invertebrates 52 leading to severe impacts on mangroves plants and macro-invertebrates (such as Marphysa, Lumbrinereis, Lillyalla, Mandippi species, Marphysa sanguinae, Notomastus latericeus, Marianida pinniger, Littorina anguilifera, Neritina owenensis, Pachymelania aurita, Pachymelania bryonensis and Crassostrea gasari etc). 52 In the Niger Delta, several macrophytes have been reported in surface water including Eichhornia crassipes, Nymphaea lotus, N. maculate, Pistia stratiotes, Salvinia nymphellula, Azolla pinnata var africana 16,45,48,53 among others.…”
Section: Freshwater Swampmentioning
confidence: 99%
“…Most fresh water resources in the area are linked to estuarine from where they emptied into the Ocean. The activities of makeshift oil refinery on Nun River estuary is having impact on the physicochemical characteristics of water, 50 sediment 51 and macro-invertebrates 52 leading to severe impacts on mangroves plants and macro-invertebrates (such as Marphysa, Lumbrinereis, Lillyalla, Mandippi species, Marphysa sanguinae, Notomastus latericeus, Marianida pinniger, Littorina anguilifera, Neritina owenensis, Pachymelania aurita, Pachymelania bryonensis and Crassostrea gasari etc). 52 In the Niger Delta, several macrophytes have been reported in surface water including Eichhornia crassipes, Nymphaea lotus, N. maculate, Pistia stratiotes, Salvinia nymphellula, Azolla pinnata var africana 16,45,48,53 among others.…”
Section: Freshwater Swampmentioning
confidence: 99%
“…The ANOVA result revealed that all samples across parameters are significantly different (p ˂ 0.05) in both wet and dry season. Gijo et al [7] assessed the impact of artisanal crude-oil refineries on the physicochemical features of the sediments of the Nun River, where they showed that the operations similarly leads to increase in total organic carbon and total petroleum hydrocarbon.…”
Section: Discussionmentioning
confidence: 99%
“…Operators of artisanal refinery in the Niger Delta are driven by pecuniary motives, in clear disregard to the environmental and health impacts of their operations. As a consequence, their operations lead to the pollution of, air, water, vegetation and soil within the vicinity of their operations [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Gijo et al [27] reported that the activities of makeshift oil refining had adversely impacted on the benthos organisms. The authors reported 30 species (from 15 families) of benthic macro invertebrates during the baseline study, and 18 species (from 10 families) after impartation of the environment by the activities of illegal refinery in Nun River estuary.…”
Section: Impacts Of Anthropogenic Activities In Surface Water Qualitymentioning
confidence: 99%
“…Gijo et al [28] reported that illegal refineries in Nun River estuary of Bayelsa state have led to pollution of the sediment of the water. The authors reported high concentration of pH, total hydrocarbon content and total organic carbon in the range of 5.11 to 6.32, 17.8mg/kg to 1125.9mg/kg and 0.34mg/kg to 51.4mg/kg, respectively.…”
Section: Impacts Of Anthropogenic Activities In Surface Water Qualitymentioning
confidence: 99%